PERANCANGAN SOLAR TRACKING SYSTEM UNTUK MENINGKATKAN DAYA PEMBANGKIT LISTRIK TENAGA SURYA BERBASIS INTERNET OF THINGS - -, Saripudin; Hermawan, Muhamad Rizki (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDCDO - 10.70428/tedc.v20i1.1492, 2026)
Electricity has become a crucial necessity that supports all human activities, making innovations in alternative energy sources such as Solar Power Plants (SPP) highly relevant, especially in Indonesia, which has abundant solar potential with an average intensity of 4.8 kWh/m². However, the use of existing static PLTS systems is considered unable to absorb energy optimally. Therefore, this research developed a solution in the form of an Internet of Things (IoT)-based Solar Tracking System through the Research and Development (R&D) method. This system was designed through systematic stages, starting from literature review to tool refinement, to ensure its performance is superior to conventional systems. As a result, the Solar Tracking System is capable of producing a stable power of 1000 watts for 2 hours at maximum load, with the advantage of a power difference of 100.26 Wp/day greater than static systems. From an economic perspective, the use of this solar tracking technology has proven to be more effective and efficient, with operational cost savings of IDR 90,000 per month. To achieve more optimal performance in the future, this research recommends increasing the capacity of solar panels to 600 Wp and using a 4000-watt inverter so that the conversion of solar energy into electricity can be maximized for community needs.